Surprise visitors - Amery, Heather; Cartwright, Stephen, 1947- ([Tulsa, Okla. : EDC], 2004)
Poppy and Sam have an eventful day when a hot air balloon lands in their field.
Keywords: Farm life -- Juvenile fiction; Hot air balloons -- Juvenile fiction; Farm life -- Fiction; Hot air balloons -- Fiction